2013
DOI: 10.1590/s1415-43662013000400004
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento hídrico e crescimento do feijão vigna cultivado em solos salinizados

Abstract: RESUMOA salinização dos solos reduz a capacidade das plantas de absorver água o que, em geral, provoca diminuição na sua taxa de crescimento. As respostas das plantas ao estresse salino são melhor correlacionadas com o potencial osmótico do que com a condutividade elétrica do extrato de saturação do solo. Com o objetivo de avaliar os efeitos do estresse salino no crescimento, evapotranspiração e potencial osmótico foliar do feijoeiro vigna [Vigna unguiculata L. (Walp.)] conduziu-se um experimento em casa de ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 13 publications
4
13
0
7
Order By: Relevance
“…For soil S1, an increase can be seen in the height of the bean plants at levels of 100 and 150% of the GR, followed by a decrease at levels of 200 and 250%, when the EC of the saturation extract of the soil was around 4.7 dS m -1 . These results are similar to those reported by Coelho et al (2013) who, working with cowpea and salinity levels (2.0, 4.0, 8.0 and 12.0 dS m -1 ), found that from an EC level of the saturation extract of the soil equal to 4.00 dS m -1 , drastic reductions in plant height were seen, with values of 75 and 85% for the sandy-loam soil and clayey-loam soil respectively. The authors explain that this reduction in the growth of the vigna bean is due to a decrease in the osmotic potential of the soil solution, which caused a greater difficulty in the absorption of water and nutrients, as well as to the possibility of there being ion toxicity due to the possible excessive accumulation of the sodium cation and the chloride anion.…”
Section: Resultssupporting
confidence: 90%
“…For soil S1, an increase can be seen in the height of the bean plants at levels of 100 and 150% of the GR, followed by a decrease at levels of 200 and 250%, when the EC of the saturation extract of the soil was around 4.7 dS m -1 . These results are similar to those reported by Coelho et al (2013) who, working with cowpea and salinity levels (2.0, 4.0, 8.0 and 12.0 dS m -1 ), found that from an EC level of the saturation extract of the soil equal to 4.00 dS m -1 , drastic reductions in plant height were seen, with values of 75 and 85% for the sandy-loam soil and clayey-loam soil respectively. The authors explain that this reduction in the growth of the vigna bean is due to a decrease in the osmotic potential of the soil solution, which caused a greater difficulty in the absorption of water and nutrients, as well as to the possibility of there being ion toxicity due to the possible excessive accumulation of the sodium cation and the chloride anion.…”
Section: Resultssupporting
confidence: 90%
“…1. Ponto de murcha permanente (-1,5 MPa); ds -Densidade do solo; dp -Densidade de partículas Com o objetivo de estimar a quantidade de sais correspondentes aos tratamentos salinos, realizou-se um ensaio preliminar utilizando uma mistura de sais composta de 2/3 de NaCl e 1/3 de CaCl 2 (Coelho et al, 2013); em seguida, procedeu-se à incubação dos solos empregando-se as concentrações de zero a 5 g dessa mistura de sais por kg de solo, na forma de uma pasta saturada (Richards, 1954). Após a incubação dos solos pelo período de 24 h, foram obtidos os extratos das pastas saturadas e se mediu a condutividade elétrica, o que proporcionou as seguintes equações: y = 6,787x + 2,634 (solo franco-arenoso); y = 4,385x + 2,526 (solo franco-argiloso); em que x é a concentração salina, em g kg -1 e y corresponde à condutividade elétrica do extrato saturado, dS m -1 .…”
Section: Methodsunclassified
“…Souza et al (2011), cultivating cowpea under saline stress, and Coelho et al (2013), using a mixture of NaCl and CaCl 2 , with 0, 4, 8 and 12 dS m -1 , cultivated cowpea under saline stress and found physiological alterations during the development of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies can be found in the literature associating salinity with water potentials (Souza et al, 2012;Adolf et al, 2013;Coelho et al, 2013;Souza et al, 2014). In addition, the evaluation of the influence of the type of salt in the irrigation water is of great relevance in studies on salinity in the soil-plant system (Melo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%